Characterization of the Transcriptomes of Lgr5+ Hair Cell Progenitors and Lgr5- Supporting Cells in the Mouse Cochlea - Cheng, Cheng; Guo, Luo; Lu, Ling; Xu, Xiaochen; Zhang, ShaSha; Gao, Junyan; Waqas, Muhammad; Zhu, Chengwen; Chen, Yan; Zhang, Xiaoli; Xuan, Chuanying; Gao, Xia; et al. (Frontiers in Molecular Neuroscience, 2017)
Cochlear supporting cells (SCs) have been shown to be a promising resource for hair cell (HC) regeneration in the neonatal mouse cochlea. Previous studies have reported that Lgr5+ SCs can regenerate HCs both in vitro and in vivo and thus are considered to be inner ear progenitor cells. Lgr5+ progenitors are able to regenerate more HCs than Lgr5− SCs, and it is important to understand the mechanism behind the proliferation and HC regeneration of these progenitors. Here, we isolated Lgr5+ progenitors and Lgr5− SCs from Lgr5-EGFP-CreERT2/Sox2-CreERT2/Rosa26-tdTomato mice via flow cytometry. As expected, we found that Lgr5+ progenitors had significantly higher proliferation and HC regeneration ability than Lgr5− SCs. Next, we performed RNA-Seq to determine the gene expression profiles of Lgr5+ progenitors and Lgr5− SCs. We analyzed the genes that were enriched and differentially expressed in Lgr5+ progenitors and Lgr5− SCs, and we found 8 cell cycle genes, 9 transcription factors, and 24 cell signaling pathway genes that were uniquely expressed in one population but not the other. Last, we made a protein-protein interaction network to further analyze the role of these differentially expressed genes. In conclusion, we present a set of genes that might regulate the proliferation and HC regeneration ability of Lgr5+ progenitors, and these might serve as potential new therapeutic targets for HC regeneration.